2014
DOI: 10.1145/2594440
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Video Sharing Propagation in Social Networks

Abstract: Modern online social networking has drastically changed the information distribution landscape. Recently, video has become one of the most important types of objects spreading among social networking service users. The sheer and ever-increasing data volume, the broader coverage, and the longer access durations of video objects, however, present significantly more challenges than other types of objects. This article takes an initial step toward understanding the unique characteristics of video sharing propagati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Therefore, publishers should be aware that it is not easy to make attractive content. This phenomenon not only indicates that only a small fraction of content achieves high popularity and, thus, has potential to spread widely through SNSs [37], but the wisdom of users also provide collaborative filtering to select flavored submissions. Moreover, high numbers of views are associated with people with high Extraversion.…”
Section: Content Popularitymentioning
confidence: 99%
“…Therefore, publishers should be aware that it is not easy to make attractive content. This phenomenon not only indicates that only a small fraction of content achieves high popularity and, thus, has potential to spread widely through SNSs [37], but the wisdom of users also provide collaborative filtering to select flavored submissions. Moreover, high numbers of views are associated with people with high Extraversion.…”
Section: Content Popularitymentioning
confidence: 99%
“…G can be represented by A, the N × N symmetric adjacency matrix, with a n,m = 1 if there exists a link between node n and m and 0 otherwise. Furthermore, we describe the effect of the routing protocol via an N × N (N − 1) routing matrix 3 , R. For our purpose, we depart from the conventional routing matrix that maps traffic to links (e.g., [44]) and instead, encode the traffic to nodes it traverses or is destined to. Accordingly, we define the routing matrix as follows:…”
Section: B Modelling the Infectious Agentmentioning
confidence: 99%
“…O RIGINATED as part of epidemiology in biology studies for modelling disease spreading [1], epidemic theory has found applications in various scientific fields, ranging from natural networks (e.g., hub protein and human brain structure [2], (online) social networks [3], etc.) to manmade infrastructures (e.g., transportation systems [4], [5], power grid [6], telecommunication and computer networks [7], [8], [9], etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Although, there are many such studies, but will discuss some of them with higher relevancy. An investigation was carried out towards sharing of the video by Li et al [75] over social networks. The authors have investigated about the pattern of information propagation.…”
Section: Studies On Multimedia Propagationmentioning
confidence: 99%